Piezo1 promotes intervertebral disc degeneration through the Ca2+/F-actin/Yap signaling axis - Fushuai Peng; Mingtong Sun; Xingzhi Jing; Fei Chen; Tong Cao; Zhenzhen Li; Tao Li (Molecular Medicine)
Abstract Background Piezo1 is a mechanically sensitive cation channel expressed in various tissues of the human body and has multiple roles in both physiological and pathological processes. However, its role in the occurrence and development of intervertebral disc degeneration (IVDD) is not fully understood. Methods In the present study, an IVDD mouse model and Piezo1 small interfering (si)RNA was used to investigate the role of Piezo1 in IVDD progression. Furthermore, the Ca2+ inhibitor, BAPTA-AM, and the F-actin cytoskeleton polymerization inhibitor, Latrunculin A, were employed to examine the roles of Ca2+ influx and cytoskeleton dynamics in Piezo1-mediated IVDD progression. Additionally, Yes-associated protein (Yap) small interfering (si)RNA was used to investigate the involvement of Yap in Piezo1-induced IVDD progression. Results The findings of the present study indicated that Piezo1 was positively associated with IVDD and that Piezo1 upregulation promoted IVDD via facilitating cartilage endplate (CEP) degeneration and calcification. The Ca2+ inhibitor, BAPTA-AM, and the F-actin cytoskeleton polymerization inhibitor, Latrunculin A, inhibited Piezo1-mediated extracellular matrix degradation and CEP chondrocyte degeneration. Moreover, it was found that Piezo1 activated Yap through an F-actin-mediated non-canonical pathway and that Yap siRNA inhibited Piezo1 upregulation-induced IVDD progression. Conclusion Overall, the results of the present study indicate that increased expression of Piezo1 is closely related to the occurrence and development of IVDD and that the Piezo1-mediated Ca2+/F-actin/Yap axis contributes to this process. Thus, targeting Piezo1 may provide a new strategy for the treatment of IVDD.